2010
DOI: 10.1055/s-0030-1262836
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response to Sorafenib in Metastatic Medullary Thyroid Carcinoma

Abstract: These data suggest a possible role for sorafenib in the treatment of progressive metastatic MTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…In an off-label observational study, five patients with progressive metastatic MTC were treated with sorafenib (400 mg twice daily). Two patients showed a partial response and two patients experienced stable disease (Frank-Raue et al 2011). In a recently published retrospective longitudinal study of 12 patients with progressive metastatic MTC, 10 patients showed stable disease (83.3%), no PR was observed.…”
Section: Sorafenibmentioning
confidence: 87%
“…In an off-label observational study, five patients with progressive metastatic MTC were treated with sorafenib (400 mg twice daily). Two patients showed a partial response and two patients experienced stable disease (Frank-Raue et al 2011). In a recently published retrospective longitudinal study of 12 patients with progressive metastatic MTC, 10 patients showed stable disease (83.3%), no PR was observed.…”
Section: Sorafenibmentioning
confidence: 87%
“…The treatment was prematurely terminated in MTC hereditary patients due to slow accrual [85]. In a similar trial, all 5 patients treated with sorafenib exhibited partial responses [86]. Recently, a study of sorafenib was conducted on advanced thyroid carcinoma patients, and partial responses were reported in six out of the 12 (50%) patients with MTC, although the small number of patients requires further prospective studies [87].…”
Section: Potential Targeted Therapies For Mtcmentioning
confidence: 99%
“…A small observational study investigated the efficacy of sorafenib in five patients with progressive MTC; after 6 months, two patients showed a partial response, and two patients exhibited SD 77. In a phase II trial, 21 patients with metastatic or locally advanced MTC, hereditary or sporadic form, were enrolled to receive 400 mg sorafenib orally twice daily.…”
Section: Review Of Therapies Targeting Receptor Tyrosine Kinasesmentioning
confidence: 99%